ANALYSIS OF WORK CULTURE, COMPETENCIES, CAREER DEVELOPMENT ON EMPLOYEE PERFORMANCE THROUGH COMPENSATION AT PT PELINDO REGIONAL 2 NORTH JAKARTA - Roy Qurrotu Ainin; Agustina Mogi; Taswanda Taryo (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effects of Work Culture, Competence, and Career Development on Employee Performance through Compensation at PT Pelindo Regional 2 North Jakarta. The research employs a quantitative and descriptive approach. The sampling technique used is probability sampling with a simple random sampling method, involving 241 respondents. The analytical tool applied in this study is Partial Least Squares–Structural Equation Modeling (PLS-SEM) version 4.0. The results of the study can be summarized as follows: (1) Work culture has a positive effect on compensation with a path coefficient of 0.195; (2) Competence has a positive effect on compensation with a path coefficient of 0.110; (3) Career development has the strongest positive effect on compensation with a path coefficient of 0.532; (4) Work culture has a negative effect on employee performance with a path coefficient of –0.066; (5) Competence has a positive effect on employee performance with a path coefficient of 0.060; (6) Career development has a negative effect on employee performance with a path coefficient of –0.204; (7) Compensation has a positive and the most dominant effect on employee performance with a path coefficient of 0.764; (8) Work culture has a positive indirect effect on employee performance through compensation with a path coefficient of 0.149; (9) Competence has a positive indirect effect on employee performance through compensation with a path coefficient of 0.084; and (10) Career development has the strongest indirect effect on employee performance through compensation with a path coefficient of 0.406. Based on these findings, it is recommended that the management of PT Pelindo Regional 2 prioritize a fair and performance-based compensation system, as it has been proven to be the most dominant factor in improving employee performance. Furthermore, career development and competence enhancement should be accompanied by proportional rewards and welfare improvements to ensure productive outcomes and encourage optimal employee contributions.